The subparietal and parietooccipital sulci: An anatomical study. Issue 6 (27th June 2013) - Gürer, Bora; Bozkurt, Melih; Neves, Gabriel; Cikla, Ulaş; Hananya, Tomer; Antar, Veysel; Salamat, Shahriar; Başkaya, Mustafa K.
<x xml:space="preserve">Abstract</x> The subparietal and parietooccipital sulci are both located on the medial surface of the brain. Both of these sulci reveal significant variability in pattern and complexity. Both subparietal and parietooccipital sulci play an important role as surgical landmarks using posterior interhemispheric parietooccipital approach to lesions located adjacent to the ventricular trigon deep to the cingulate gyrus. The aim of this study is to analyze variations in the patterns of the subparietal and parietooccipital sulci and to emphasize their surgical importance. Fifty‐six formalin‐fixed cadaveric cerebral hemispheres from 28 adult humans are examined. Subparietal and parietal sulci patterns, variations and their relationship with the cingulate sulcus are studied according to the terminology introduced by Ono et al. The H‐pattern was observed in 50% (n = 28) of all hemispheres, being the most common pattern of the subparietal sulcus. The Straight pattern was observed in the 30.4% (n = 17) of all hemispheres, being the most common pattern of the parietooccipital sulcus. Furthermore, more detailed results among the patterns, connections, side branches and the relationship with the adjacent sulci are given. Our study further confirms the complexities in the patterns of the subparietal and parietooccipital sulci and demonstrates that these sulci fall within an expected range of variations. Better knowledge of these variations will further help neurosurgeons to navigate easily during approaches involving the medial surface of the parietal lobe. Clin. Anat. 26:667–674, 2013. © 2013 Wiley Periodicals, Inc.